AUTISM SPECTRUM DISORDER IN THE CONTEXT OF PUBLIC SCHOOLS: CONTRIBUTIONS OF PHYSICAL EDUCATION TO THE DEVELOPMENT OF LANGUAGE: MEDIATION, BODY AND EMBODIED COGNITION - Bessa, Valéria de Nazaré de Paula; Palheta, Éder do Vale; Palmeira, Biratan dos Santos; da Silva, Luciano Barros; Cabral, Mauricio Martins; da Costa, Márcia de Araujo; dos Santos, Marco Antônio Barros; Souza, Danilo da Costa (Seven Editora, 2026)
This article analyzes the contributions of school Physical Education to the development of language in students with Autism Spectrum Disorder (ASD) in the context of public schools. This is qualitative research with a theoretical-bibliographic approach, grounded in Bardin’s Content Analysis (2016), with a corpus composed of 38 scientific works selected from indexed databases SciELO, ERIC, Scopus and CAPES Journals Portal, published between 2020 and 2025, following a protocol compatible with PRISMA guidelines. The theoretical framework articulates Gardner’s Theory of Multiple Intelligences (1995), critically repositioned in light of contemporary studies on embodied cognition and language, with Vygotsky’s mediation perspective and recent literature on ASD, linguistic development, and school inclusion. Results indicate that Physical Education, when organized with pedagogical intentionality and grounded in inclusive principles, constitutes a relevant space for language mediation, enabling forms of expression that transcend orality including the articulated use of bodily practices and Augmentative and Alternative Communication (AAC) resources. The analysis reveals a productive tension between structured behavioral approaches and sociointeractionist perspectives, whose integration tends to produce more consistent outcomes in school contexts. It is concluded that the integration of body, movement, and language constitutes a relevant pedagogical axis for expanding the communicative repertoire of students with ASD, with direct implications for teacher education and inclusive education policies.